PENINGKATAN PEMASARAN PRODUK BERBASIS TEKNOLOGI INFORMASI PADA UKM KERAJINAN PERAK DAN BATU ALAM DI BALI - Putra, I.G.N.A.C.; Karyawati, A.A.I.N.E.; Sanjaya ER, N.A.; Giri, G.A.V.M.; Wibawa, I.G.A. (Buletin Udayana Mengabdi, 2023)
During the COVID-19 pandemic, many businesses in Bali were affected, especially those related to the tourism sector. One of the businesses affected is TwinSilver, TwinSilver is an SME of Silver and Natural Stone Crafts having its address at Jalan Siulan, East Denpasar. Under normal conditions, TwinSilver conducts direct marketing, where TwinSilver opens outlets/stands in Sanur tourist spots which are visited by many tourists, both domestic and foreign. In the midst of the current conditions TwinSilver is no longer able to do direct marketing and the stand was closed for several months. Seeing the condition of TwinSilver SMEs, it is necessary to utilize information technology so that the business can continue to run. Information technology that will be applied includes creating an online stand or creating a digital store. So it is hoped that with an online store, sales can still be carried out by TwinSilver SMEs even in the midst of the Covid-19 pandemic. Keywords: information technology, online shop